Industrial waste bioconversion into surfactants by Rhodococcus erythropolis IMV Ac-5017, Acinetobacter calcoaceticus IMV B-7241 and Nocardia vaccinii IMV B-7405 - Pirog, Tatiana; Shulyakova, Mariya; Kliuchka (Nykytyuk), Lilia; Antoniuk, Svitlana; Elperin, Igor (My University, 2017)
The aim of the work is to realize an alternative processing of toxic industrial waste into surfactants by strains Rhodacoccus erythropolis IMV Ac-5017, Acinetobacter calcoaceticus IMV B-7241 and Nocardia vaccinii IMV B-7405 for remediation of environment. The studied strains were grown in liquid media containing such sources of carbon as waste (fried) sunflower oil. technical glycerol (by product of biodiesel production), and aromatic compounds. The synthesis of surfactants was evaluated by emulsification index. conditional concentration of surfactants and concentration of extracellular surfactants, which was determined gravimetrically after their extraction from supernatant by the mixture of methanol and chloroform. The concentration of oil in water and soil was analyzed by gravimetric method after extaction with hexane.
Keywords: industrial waste; microbial surfactants; environment remediation; промислові відходи; мікробні поверхнево-активні речовини; ре медіація довкілля; промышленные отходы; микробные поверхносно-активные вещества; ремедиация окружающей среды; кафедра біотехнології і мікробіології; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка